Surgical treatment of congenital coronary artery fistula. - John, S (1981)
Six patients with congenital coronary artery fistula underwent successful corrective surgery. Precise diagnosis was established either by retrograde aortography or more recently by selective arteriography. The left coronary artery was involved in four and the right in two cases. The fistula communicated with the right ventricle in three and the right atrium in three subjects. The operative approach is dictated by the site of entry of the vessel into the cardiac chamber. The use of cardiopulmonary bypass for intracardiac repair allows accurate closure of the fistula thereby reducing the chances of recurrence. A follow-up of one to seven years showed that all patients are asymptomatic and leading normal lives.